Dividend policy on controlling and non-controlling shareholders: case in Indonesia - Novi Swandari Budiarso (Investment Management & Financial Innovations, 2019)
The purpose of this study is to examine dividend policy on both the controlling and non-controlling shareholders based on assumptions according to theories of life cycle, and free cash flow.The sample for this study is 241 listed firm in Indonesia Stock Exchange during the period from 2010 to 2015. This study divides the sample based on quartiles and analyzes it by conducting logistic regression with significant rate at 0.05. This study provides the evidences that: (1) firms as dividend payers tend not distribute their dividend for controlling shareholders and non-controlling shareholders while the composition for both shareholders are almost equal; (2) firms as dividend payers also have tendency not to distribute dividend on controlling shareholders when this shareholders have largest percentage of ownership; and (3) firms as dividend payers tend not distribute dividend on non-controlling shareholders while they have lowest retained earnings.The findings imply that life cycle theory and free cash flow theory can explain the behavior of dividending policy on controlling shareholders and non-controlling shareholders depend on their circumstances.The study uses alternative measurement for non-controlling shareholders as this variable together with controlling shareholders are moderating the other independent variables for testing the model of dividend policy.